Beyond Budgeting for Adaptive Financial Management in Uzbekistan’s Banking Sector: Melampaui Penganggaran untuk Manajemen Keuangan Adaptif di Sektor Perbankan Uzbekistan - Soatov Farhod Komiljon o‘g‘li (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: The banking sector is undergoing significant transformation, necessitating adaptive financial management practices. Traditional budgeting, characterized by rigid annual plans and fixed targets, has proven inefficient in dynamic economic environments. Specific Background: Beyond Budgeting, introduced by Hope and Fraser, offers an alternative approach emphasizing rolling forecasts, decentralized decision-making, and adaptive performance evaluation. Knowledge Gap: Despite its success in global banking institutions like Svenska Handelsbanken and UBS, limited research explores its applicability in emerging markets, particularly in Uzbekistan. Aims: This study examines the limitations of traditional budgeting, the advantages of Beyond Budgeting, and its potential implementation in Uzbekistan’s banking sector. Results: Findings highlight that Beyond Budgeting enhances financial flexibility, operational efficiency, and customer responsiveness. Key enablers include investment in financial analytics, strategic decentralization, and regulatory adaptation. Novelty: This study provides a tailored roadmap for Beyond Budgeting adoption in Uzbekistan’s banking sector, addressing cultural resistance and regulatory challenges. Implications: Transitioning to Beyond Budgeting can significantly improve financial performance, enabling banks to navigate economic volatility and enhance long-term competitiveness. These insights contribute to the broader discourse on financial management innovation in emerging markets. Highlights: Traditional budgeting is inefficient in dynamic banking environments. Explore Beyond Budgeting’s benefits and applicability in Uzbekistan’s banking sector. Enhances financial flexibility, efficiency, and competitiveness in emerging markets. Keywords: Beyond Budgeting, banking sector, financial management, budgeting alternatives, rolling forecasts, decentralized decision-making, performance evaluation, cost efficiency, strategic financial planning.